Alterations of phenolic compounds in red raspberry juice induced by high-hydrostatic-pressure and high-temperature short-time processing. (January 2021) - Zhang, Wentao; Liang, Liya; Pan, Xin; Lao, Fei; Liao, Xiaojun; Wu, Jihong
Abstract: Most studies on health-promoting attributes of red raspberries have been conducted using extracts or freeze-dried powders instead of commercially processed products. This work aimed to trace the alterations of phenolic compounds in HHP- and HTST-treated juices. In total, 151 phenolic compounds were identified: 13 and 26 differential phenolics were discriminated in HHP- and HTST-treated juices, respectively. The alterations of phenolic compounds could be related to the increased oxidative stress derived from the indirect oxidation and thermal degradation. HTST processing promoted the release of free phenolic acids from their conjugated forms, while HHP processing could maximize the flavonol glycosides. Furthermore, morin was observed with a 7400-fold increase in HTST-treated juice, indicating the potential use for juice authenticity. Generally, HHP processing showed less impact on phenolic profiles in comparison with HTST processing. These findings provide novel insights into the impacts of sterilization processes on phenolic compounds in red raspberries. Highlights: This is the first metabolomics investigation on the impacts of sterilization on red raspberries. The alterations of phenolic compounds could be related to the increased oxidative stress. Morin could be a potential biomarker for thermal processed juice.